Germination and Seedling Vigour of Soybean (Glycine max) and Blackgram (Vigna mungo) as Affeced by Priming Methods in Lamjung - Khanal, Sugam; Shrestha, Sudikshya (Journal of the Institute of Agriculture and Animal Science, 2024)
To address poor germination and seedling establishment in legume cultivation this study explored the impact of seed priming with different concentrations of gibberellic acid (GA3) compared to hydropriming on soybean and blackgram. Two separate experiments were conducted with four replications each in Completely Randomized Design. The seeds underwent hormonal priming with varying concentrations of GA3 - 50 ppm, 75 ppm, 100 ppm and 125 ppm and hydro-priming at the Agronomy laboratory of Lamjung Campus. For soybean, 100 ppm GA3 produced the best results (P<0.05) in terms of germination rate (99%), root and seedling length, and seedling vigor index (2054.20). Meanwhile, 50 ppm GA3 showed the fastest germination and better germination index (237.00) compared to other treatments (P<0.05). In blackgram, 50 ppm GA3 treatment resulted in 100% germination and significant effects on various parameters, including coefficient of velocity of germination and germination index (244.75) while 75 ppm GA3 exhibited the fastest germination time and longest length of root (10.85 cm) (P<0.05). Hydropriming improved overall seedling characteristics like seedling length and seedling vigor index (2074.16) (P<0.05). This highlights the effectiveness of hydro-priming, priming with 50 ppm GA3 for blackgram and 100 ppm GA3 for soybean, emphasizing the importance of priming methods.